Porous interbody fusion cage design via topology optimization and biomechanical performance analysis. Issue 6 (26th April 2023) - Li, Nan; Zhang, Yang; Tang, Qiaohong; Wang, Hongkun; He, Da; Yao, Yan; Fan, Yubo
Abstract: The porous interbody fusion cage could provide space and stable mechanical conditions for postoperative intervertebral bone ingrowth. It is considered to be an important implant in anterior cervical discectomy and internal fixation. In this study, two types of unit cells were designed using topology optimization method and introduced to the interbody fusion cage to improve the biomechanical performances of the cage. Topology optimization under two typically loading conditions was first conducted to obtain two unit cells (O-unit cell and D-unit cell) with the same volume fraction. Porous structures were developed by stacking the obtained unit cells in space, respectively. Then, porous interbody fusion cages were obtained by the Boolean intersection between the global structural layout and the porous structures. Finite element models of cervical spine were created that C5-C6 segment was fused by the designed porous cages. The range of motion (ROM) of the cervical spine, the maximum stress on the cage and the bone graft, and the stress and displacement distributions of the cage were analyzed. The results showed the ROMs of C5-C6 segment in D-unit cell and O-unit cell models were range from 0.14° to 0.25° under different loading conditions; the cage composed of the D-unit cells had a more uniform stress distribution, smaller displacement on cage, a more reasonable internal stress transfer mode (transmission along struts of the unit cell), and higher stress on the internal bone graft (0.617 MPa). In conclusion, the optimized porous cage is a promising candidate for fusion surgery, which would avoid the cage subsidence, and promote the fusion of adjacent endplates.